A mixed methods exploration of intensive care unit nurses' perception of handling oxygen therapy to critically ill patients. (June 2019) - Bunkenborg, Gitte; Bundgaard, Karin
Abstract: Objectives: Nurses handle supplementary oxygen to intensive care unit patients as part of their daily practise. To secure patients of optimal and safe care, knowledge of nurses' perception of this practise, including influencing factors for adjusting oxygenation levels is essential. This study aimed to explore intensive care nurses' perception of handling oxygenation and of factors that govern and influence this practise. Research methodology/design: A mixed methods approach was applied comprising six focus group interviews, conducted in February/March 2017, leading to construction of a questionnaire distributed to 535 ICU nurses in September 2017. Following a process of content analysis, the findings were discussed against Gittell's framework for relational coordination. Setting: Intensive care units in rural, urban and university hospital settings. Main outcome: A deeper understanding of nurses' perception of handling oxygenation to patients in the intensive care unit. Findings and results: Findings are presented through the categories Treatment Guidance, Nursing Practise, Knowledge and Competences and Inter-professional Collaboration . Conclusion: Nurses' practise of handling supplementary oxygen therapy to the intensive care patient is influenced by day-by-day physician prescribed upper and lower limits for pO2 and pCO2, by nurses' understanding of the individual clinical patient situation and by knowledge of pros and cons in relation to oxygen therapy including observational and clinical assessment expertise. Establishing working environments in the intensive care unit setting based on mutual inter- and intra-professional respect may contribute to enhance safe and high quality patient care.